In Hospital Outcome of Pharmaco-invasive Therapy versus Primary PCI In ST-segment elevation Myocardial Infarction in Dhaka, Bangladesh - Taimur, Syed Dawood Md; Khan, Saidur Rahman (University Heart Journal, 2023)
Background & Objectives: In many low middle income countries (LMIC), it is difficult to treat patients with ST-segment elevation Myocardial Infarction (STEMI) with timely PPCI. Thus, many undergo fibrinolysis. Whether early fibrinolysis followed by timely coronary angiography provides a clinical outcome similar to that of primary percutaneous coronary intervention (PPCI) after acute STEMI in LMIC settings remains a question. In this observational study we primarily aimed to compare in-hospital outcomes of primary PCI versus pharmaco-invasive strategy (immediate fibrinolysis followed by coronary angiography with possible PCI within 3-24 hours) for reperfusion in eligible patients with STEMI at a tertiary cardiac care center. Methods: This prospective observational study was done in Ibrahim Cardiac Hospital & Research Institute, Dhaka from April 2022 to July 2022 where consecutive patients presenting with STEMI were enrolled and divided into two groups: those who underwent primary PCI (Group-I) and those who underwent immediate fibrinolysis with subsequent coronary angiography with PCI within 3 to 24 hours (Group-II). The main outcomes analyzed were all-cause death, cardiogenic shock, acute left ventricular failure, life threating arrhythmia, acute stent thrombosis, CVD, Contrast induced nephropathy (CIN), re-infarction, target-vessel revascularization, and major bleeding up to 7 days. Results: A total 122 patients presented with acute STEMI, 61 in each group. One group underwent primary PCI and another group treated with fibrinolysis by tenecteplase. The mean age of the studied patients was 53.86±9.72 years (range 18-75 years). Eighteen percent of patients presented with Extensive Anterior MI,19.7% showed Anterior MI, 21.3% showed Antero-septal MI, 21.3% showed Inferior MI, 9.8% showed Inferior with posterior and 3.3% showed Lateral MI. 35.5% had Single vessel disease, 31.1% had double vessel disease,28.7% had triple vessel disease, LM with LAD was 0.8% and 0.8% had recanalized infarct related artery in both groups overall. In group-I 45.9% of PPCI were undertaken in LAD and 32.8% patient. of group-II was done PCI in LAD. There were no significant differences between two groups in primary outcome and mortality. Conclusion: Immediate fibrinolysis followed by coronary angiography within 3-24 hours resulted in similar short-term outcomes in patients with STEMI compared to PPCI. Our study suggests that, compared with PPCI, fibrinolysis performed in the hospital setting is associated with similar mortality rates, acute CVD, CIN and acute left ventricular failure in with PPCI than STEMI. University Heart Journal 2023; 19(1): 10-14